Social Assessment Builds a Project for People and Parks in Argentina - World Bank (Washington, DC, 2012)
In the Argentina Biodiversity Conservation Project, a social assessment (SA) helped the Government of Argentina/World Bank team develop a cooperative approach to protected areas management. Social analysis and participatory research helped the task team understand the range of potential social impacts and risks to people living in proposed protected areas, and to the project itself. The resulting recommendations were put forth in a mitigation plan and a public participation/training plan for the project that will promote collaboration among the public sector, private sector, and non-governmental organizations (NGOs), increased community participation in protected areas management, and sustainable land use practices that will reduce the threats to protected areas.